2016
DOI: 10.1177/0265407516640387
|View full text |Cite
|
Sign up to set email alerts
|

Dating out is intercultural

Abstract: Romantic relationships are situated within broader cultural and family contexts, and this may be particularly salient to those in intergroup relationships. This study examined variations in young adults' experiences with intercultural romantic relationships by ethnicity and immigrant generation. A sample of ethnically diverse young adults (N ¼ 628; Asian, Latino, and European background) reported on self and parent attitudes toward dating outside of one's own culture, own current dating status, and disapproval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…A qualitative study of a diverse group of second-generation immigrants highlighted that some second-generation immigrant youth may disagree with their parents about when they can date and who they should marry, with parents generally favoring culturally similar partners (Nesteruk & Gramescu, 2012). Another study surveyed a diverse group of youth of Asian, Latino, and European ancestry and found that first- and second-generation youth were more likely than third-generation youth (defined by the authors as the child and parents born in the United States) to experience conflicts with their parents about dating (Shenhav, Campos, & Goldberg, 2017). Rani, Mitschke, Black, and Pearson (2019) explored the perspectives of Karen American youth (a refugee group from Burma) and highlighted how youth face challenges in dating related to intergenerational cultural differences in dating acceptability, which may play a role in how much youth are willing to talk with their parents about relationships.…”
Section: Introductionmentioning
confidence: 99%
“…A qualitative study of a diverse group of second-generation immigrants highlighted that some second-generation immigrant youth may disagree with their parents about when they can date and who they should marry, with parents generally favoring culturally similar partners (Nesteruk & Gramescu, 2012). Another study surveyed a diverse group of youth of Asian, Latino, and European ancestry and found that first- and second-generation youth were more likely than third-generation youth (defined by the authors as the child and parents born in the United States) to experience conflicts with their parents about dating (Shenhav, Campos, & Goldberg, 2017). Rani, Mitschke, Black, and Pearson (2019) explored the perspectives of Karen American youth (a refugee group from Burma) and highlighted how youth face challenges in dating related to intergenerational cultural differences in dating acceptability, which may play a role in how much youth are willing to talk with their parents about relationships.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are situations in which different cultural norms are at once activated, salient, and opposed to one another. Such normative cultural conflicts are typically encountered during major life decisions, such as when choosing a romantic partner or a career path (Lalonde & Gigu ere, 2008;Shenhav, Campos, & Goldberg, 2017). Such normative cultural conflicts are typically encountered during major life decisions, such as when choosing a romantic partner or a career path (Lalonde & Gigu ere, 2008;Shenhav, Campos, & Goldberg, 2017).…”
Section: Conflicts Between Cultural Normsmentioning
confidence: 99%
“…Conflict between the norms becomes inevitable (Gigu ere et al, 2010). Such normative cultural conflicts are typically encountered during major life decisions, such as when choosing a romantic partner or a career path (Lalonde & Gigu ere, 2008;Shenhav, Campos, & Goldberg, 2017). As these conflicts possibly involve being rejected from one's cultural ingroup, they can generate significant distress (Gigu ere et al, 2010).…”
Section: Conflicts Between Cultural Normsmentioning
confidence: 99%
“…On the other hand, daughters' romantic relationships may be subject to greater scrutiny than sons' precisely because they are expected to be kin-keepers. In general, studies find that men report less disapproval from parents over interracial/ethnic dating than women (Park, Vo, & Tsung, 2009;Shenhav, Campos, & Goldberg, 2016). To summarize, it is possible that parents' reactions to partner choice may differ by offspring gender.…”
Section: The Role Of Race/ethnicity and Gendermentioning
confidence: 99%